2005
DOI: 10.1007/s00359-005-0071-8
|View full text |Cite
|
Sign up to set email alerts
|

Antennal lobe projection destinations of Helicoverpa zea male olfactory receptor neurons responsive to heliothine sex pheromone components

Abstract: We used single sensillum recordings to define male Helicoverpa zea olfactory receptor neuron physiology followed by cobalt staining to trace the axons to destination glomeruli of the antennal lobe. Receptor neurons in type A sensilla that respond to the major pheromone component, (Z)-11-hexadecenal, projected axons to the cumulus of the macroglomerular complex (MGC). In approximately 40% of these sensilla a second receptor neuron was stained that projected consistently to a specific glomerulus residing in a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 44 publications
4
43
1
Order By: Relevance
“…Thus, specific sensory neuron types, randomly distributed in the periphery, project to distinct addresses in the antennal lobe/olfactory bulb. These findings are in full agreement with results from tracing of physiologically characterized receptor neurons in several moth species (Hansson et al 1995;Berg et al 1998Berg et al , 2005Lee et al 2006).…”
Section: Introductionsupporting
confidence: 93%
“…Thus, specific sensory neuron types, randomly distributed in the periphery, project to distinct addresses in the antennal lobe/olfactory bulb. These findings are in full agreement with results from tracing of physiologically characterized receptor neurons in several moth species (Hansson et al 1995;Berg et al 1998Berg et al , 2005Lee et al 2006).…”
Section: Introductionsupporting
confidence: 93%
“…This type of ORN serves as a catch-all for three different behaviorally antagonistic pheromone-related compounds, including Z9-14:Ald, emitted by several non-conspecifi cs. At the same time, the second ORN in the H. zea C-type sensilla responsive to Z9-16:Ald and involved in attraction, also responds well to Z9-14:Ald and sends its axon to the dorso-medial glomerulus of the MGC involved in attraction [Lee et al, 2005]. Thus it may be that the same receptor is co-expressed with a different receptor on two different types of ORNs and could modulate male behavior in ways important to the evolution of sex pheromone blends by broadening the responsiveness of ORNs.…”
Section: Co-expression Of Two Odorant Receptors On the Same Orn Explamentioning
confidence: 99%
“…In some classes of sensilla (such as A-type), one of these co-compartmentalized ORNs is always completely silent to any tested odorants, whereas the other responds readily to a pheromone component. The presence of silent ORNs has been revealed by cobalt staining of pairs of ORNs in A-type sensilla of H. zea [Lee et al, 2005], H. subfl exa , and H. virescens [Berg et al, 1998]. Cobalt staining also revealed that a silent ORN is also present in the B-type sensilla of H. subfl exa [S.G. Lee et al, unpubl.…”
Section: Odorant Receptor Expression Dictates Orn Tuning Profi Lesmentioning
confidence: 99%
See 1 more Smart Citation
“…Single sensillum recordings have shown that in most heliothine moths, Heliothis and Helicoverpa species, divergent types of sensilla house OSNs that are tuned to different principal sex pheromone components [9]–[14], [26][28]. Typically, a larger fraction of OSNs responds to the major components of sex pheromones in heliothine moths [11], [13], [14], [29], [30], possibly to increase the sensitivity for pheromones. Baker et al (2012) recently suggested that the functional reason for over-representation of OSNs for major pheromone components on moth antennae is to accommodate the greater dynamic flux rates encountered for the major pheromone component while maintaining overall response ratios [31].…”
Section: Introductionmentioning
confidence: 99%